Animation of cultural memory in Zbraslav using examples of the events Celebrations of Eliška Přemyslovna and Rozmarná plovárna - Hrdá, Anna (2023)
This Bachelor’s thesis – Animation of cultural memory in Zbraslav using examples of the events Celebrations of Eliška Přemyslovna and Rozmarná plovárna – discusses animation processes, animation of cultural memory and genius loci in Zbraslav. It analyzes the organization of the events Celebrations of Eliška Přemyslovna and Rozmarná plovárna and examines the motivation for organizing these events. The thesis describes both events in terms of size, duration, financing, type of event, organizational subject, function of the event and motivation of the animator. As part of the research, interviews with the organizers and questionnaire surveys aimed at the visitors of both events were conducted. By comparing the two events, it became clear that although both animate cultural memory and historical figures, there are big differences in the form and method of animation between the two. However, they correspond with the spirit and significance of the animated personalities.